Short interest, institutional ownership, and stock returns - Asquith, Paul; Pathak, Parag A.; Ritter, Jay R. (Journal of Financial Economics, 2005)
Stocks are short-sale constrained when there is a strong demand to sell short and a limited supply of shares to borrow. Using data on both short interest (a proxy for demand) and institutional ownership (a proxy for supply) we find that constrained stocks underperform during the period 1988–2002 by a significant 215 basis points per month on an equally weighted basis, although by only an insignificant 39 basis points per month on a value-weighted basis. For the overwhelming majority of stocks, short interest and institutional ownership levels make short selling constraints unlikely.